PERBANDINGAN PENERAPAN PIDANA TERHADAP PENYEBARAN KONTEN PORNOGRAFI DI MEDIA SOSIAL - Krisencia Indah Permata Celina Rere (2021)
The purpose of this study was to determine the context of the comparison with two cases of applying criminal law against perpetrators of the crime of spreading pornographic videos into social media applications in the Bandung High Court Decision Number 68/Pid/2011/PT.BDG and the South Jakarta District Court Decision Number 134/Pid. .Sus/2021/PN.JKT SEL. The research used is a normative legal research type, using a statutory approach and a case approach. The results obtained in this study, namely the application of the Criminal Code in the decision Number 134/Pid.Sus/2021/PN.JKT SEL are in accordance with the actions taken by the defendant who were proven legally and convincingly guilty as the second alternative charge, namely Article 27 paragraph (1) Jo Article 45 paragraph (1) of the ITE Law, while in the Bandung High Court Decision Number 68/Pid/2011/PT.BDG the defendant was proven legally to have violated Article 4 jo. 29 Pornography Law. The decision on this case was based on the consideration of the Panel of Judges because of the available evidence and witnesses, the Panel of Judges decided that the defendant was legally proven to have committed the crime of spreading pornographic content. Furthermore, Gisel's role is more precisely said to be a victim because he made or produced the video for his personal interests and had no intention to disseminate it to the general public. Keywords: Comparison of Crime, Application of the Crime of Spreading Pornography, Immoral Crimes, Social Media.